Sintesis dan Karakterisasi Katalis Karbon Kulit Kolang-Kaling (Arenga Pinnata) Tersulfonasi untuk Produksi Biodiesel Dari Palm Fatty Acid Distillate - Simbolon, Ranita; Nizar, Umar Kalmar (Periodic, 2024)
Indonesia is developing alternative energy, namely biodiesel. In producing biodiesel, catalysts are needed. One of the catalysts is a solid acid catalyst that can be synthesized from organic waste containing cellulose, hemicellulose and starch. The organic waste used in this study was a peel of sugar palm fruit. The purpose of this study is to determine the physicochemical properties of carbon catalysts from peel of sugar palm fruit that have been synthesized by calcination and sulfonation methods using H2SO4 and study some of the properties of biodiesel resulting from the esterification reaction between PFAD and methanol using a peel of sugar palm fruit sulfonated carbon catalyst. The synthesis of this catalyst uses a calcination method with a temperature variation of 250oC – 400oC and a sulfonation method using H2SO4. The resulting catalyst is characterized by FTIR, XRD and acid site. Then, catalysts are applied in producing biodiesel. The resulting biodiesel is tested for its biodiesel properties. The results of the study obtained that the highest number of acid sites in the carbon from the peel of sugar palm fruit was a calcination temperature of 300oC (K3-300) of 0.03538 mmol.g-1. The results of the FTIR characterization analysis showed that the sulfonate group was successfully substitution into the carbon surface which can be observed in the area of 1300-1000 cm-1. This area features two twin peaks that are characteristic of symmetrical and asymmetric sulfonate groups. Meanwhile, the result of XRD characterization is that the cholang-kaling skin catalyst forms a catalyst with an amorphous structure. The highest test results of the kolang-kaling skin acid site were at the optimum temperature, namely K3-300 of 0.03538 mmol.g-1. The K3-300 catalyst managed to convert the FFA percent to FAME by 48.33%.